Advanced computer architecture and parallel processing - El-Rewini, Hesham (Wiley series on parallel and distributed computing., 2005)
Computer architecture deals with the physical configuration, logical structure, formats, protocols, and operational sequences for processing data, controlling the configuration, and controlling the operations over a computer. It also encompasses word lengths, instruction codes, and the interrelationships among the main parts of a computer or group of computers.